2023
DOI: 10.1186/s12906-023-04275-3
|View full text |Cite
|
Sign up to set email alerts
|

Artichoke (Cynara scolymus L.) water extract alleviates palmitate-induced insulin resistance in HepG2 hepatocytes via the activation of IRS1/PI3K/AKT/FoxO1 and GSK-3β signaling pathway

Aihua Deng,
Yun Wang,
Kerui Huang
et al.

Abstract: Background Artichoke (Cynara scolymus L.) is a typical element of a traditional Mediterranean diet and has potential health advantages for insulin resistance (IR) and type 2 diabetes mellitus (T2DM). This study aims to evaluate the effect and underlying mechanism of artichoke water extract (AWE) on palmitate (PA)-induced IR in human hepatocellular carcinoma (HepG2) cells. Methods The effect of AWE on cell viability was determined using CCK8 assay. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that water extract from artichoke ameliorates high-fat diet-induced non-alcoholic fatty liver disease in rats ( 74 ). Deng’s study ( 75 ) demonstrated that artichoke water extract (AWE) reduced the expression of acid enol phosphoenolpyruvate carboxykinase (PEPCK) and glucose-6-phosphatase (G6Pase), and inhibited insulin resistance to improve glucose metabolism. Meanwhile, AWE also inhibited the endoplasmic reticulum stress to protect HepG2 cells.…”
Section: Lifestyle Interventions Of Mafldmentioning
confidence: 99%
“…Previous studies have shown that water extract from artichoke ameliorates high-fat diet-induced non-alcoholic fatty liver disease in rats ( 74 ). Deng’s study ( 75 ) demonstrated that artichoke water extract (AWE) reduced the expression of acid enol phosphoenolpyruvate carboxykinase (PEPCK) and glucose-6-phosphatase (G6Pase), and inhibited insulin resistance to improve glucose metabolism. Meanwhile, AWE also inhibited the endoplasmic reticulum stress to protect HepG2 cells.…”
Section: Lifestyle Interventions Of Mafldmentioning
confidence: 99%
“…Additionally, studies have reported that aqueous extracts of C. scolymus leaves attenuate oxidative stress and lipoprotein dyshomeostasis in rats fed on high-cholesterol diet. The hepatoprotective effects were elucidated by quantifying the markers of oxidative stress, inflammatory cytokines, insulin signaling, and hepatic gene expression related to lipid metabolism [ 9 ].…”
Section: Introductionmentioning
confidence: 99%